What's up, Tiger Lilyn - Nicholson, James H.; Arkoff, Samuel Z.; Saperstein, Henry G.; Allen, Woody; Bercovitch, Reuben (Independent classics collection, 1966)
Ridiculous and wholly inappropriate English dialogue is dubbed over a Japanese imitation of a James Bond film. The plot involves an international hunt for a top-secret recipe for the world's best egg salad.